2021
DOI: 10.1108/ijshe-07-2020-0251
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between dispositions to think critically and sustainability concern in HESD

Abstract: Purpose Higher education is uncertain which sustainability-related education targets should be sought and monitored. Accepting that something needs to be measurable to be systematically improved, the authors explored how measures relate to potential targets. This paper aims to focus on dispositions to think critically (active open-minded thinking and fair-minded thinking in appraising reasoning) as measures and explored how they related to sustainability concern as an indicative educational target. Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Regarding Shephard, the fourth author with more published documents, it is observed that this author follows very closely the themes also studied by the aforementioned authors. Effectively, topics such as sustainability [50,51], sustainable development in higher education [52][53][54] and sustainability and competences in higher education [55,56], are themes addressed by this author.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…Regarding Shephard, the fourth author with more published documents, it is observed that this author follows very closely the themes also studied by the aforementioned authors. Effectively, topics such as sustainability [50,51], sustainable development in higher education [52][53][54] and sustainability and competences in higher education [55,56], are themes addressed by this author.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%